The impact of the media: on character formation, ethical education, and the communication of values in late modern pluralistic societies - Welker, Michael; Hagen, Jürgen von; Witte, John; Pickard, Stephen K. (Evangelische Verlagsanstalt, 2022)
Frontmatter -- Cover -- Titel -- Impressum -- Table of Contents -- Acknowledgments -- Preface to the Series -- Introduction -- Part One: Media and Values -- The Texture of Values in the Media of Media Society: Preliminary Observations -- Part Two: Media, Economics, and Ethics -- Media Economics: Overview and Recent Developments -- Clicks, Likes, and Cookies: The Trading of Active and Possible Attention in Media-Saturated Societies -- Are Social Networks Media?: The Problematic Financial Classification as Communication Services Companies -- Part Three: Media, Values, and Crises -- Datafied Media and the Silent Derangement of Ethics -- Seeing a Crisis Through Media: Narrating the Coronavirus Pandemic in the Early Twenty-First Century -- Contemporary Media and the Crisis of Values -- Part Four: Ethical Potentials and Problems in Media Communication -- Why Moral Agency Is Crucial to Mainstream Cinema -- Trolls and Bullies: A South African Case Study of Cyber-Misogyny and the Media -- "Attitude" Can Damage Attitude When Journalists Abuse Their Power -- Backmatter -- Contributors -- Weitere Veröffentlichungen.